Hannibal - Harris, Thomas, 1940- (Hannibal Lecter, 1999)
Years after his escape, posing as scholarly Dr. Fell, curator of a grand family's palazzo, Hannibal lives the good life in Florence, playing lovely tunes by serial killer/composer Henry VIII and killing hardly anyone himself.Clarice is unluckier: in the novel's action-film-like opening scene, she survives an FBI shootout gone wrong, and her nemesis, Paul Krendler, makes her the fall guy.Clarice is suspended, so, unfortunately, the first cop who stumbles on Hannibal is an Italian named Pazzi, who takes after his ancestors, greedy betrayers depicted in Dante's Inferno.Pazzi is on the take from a character as scary as Hannibal:Mason Verger.When Verger was a young man busted for raping children, his vast wealth saved him from jail.All he needed was psychotherapy--with Dr. Lecter.Thanks to the treatment, Verger is now on a respirator, paralyzed except for one crablike hand, watching his enormous, brutal moray eel swim figure eights and devour fish.His obsession is to feed Lecter to some other brutal pets.